After Eighty Study - Mayfield, Eleanor (MD Conference Express, 2015)
Invasive intervention following NSTEMI or unstable angina pectoris in the population aged ≥ 80 years is controversial. In the After Eighty Study, early invasive intervention proved superior to conservative management in a study population with a mean age of 85 years.